2003
DOI: 10.1021/es0303440
|View full text |Cite
|
Sign up to set email alerts
|

A Survey of Perfluorooctane Sulfonate and Related Perfluorinated Organic Compounds in Water, Fish, Birds, and Humans from Japan

Abstract: Occurrence of perfluorooctane sulfonate (PFOS) in the tissues of humans and wildlife is well documented. In this study, concentrations and distribution of PFOS, perfluorohexane sulfonate (PFHS), and perfluorobutane sulfonate (PFBS) were determined in samples of surface water, fish and bird blood and livers, and human blood collected in Japan. Notable concentrations of PFOS were found in surface water and fish from Tokyo Bay. PFOS was found in all of the 78 samples of fish blood and liver analyzed. Based on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

20
287
3
5

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 454 publications
(315 citation statements)
references
References 20 publications
20
287
3
5
Order By: Relevance
“…The concentration of PFBS in this study was comparable to that in other coastal regions, such as Catalonia and Cantabrian Sea in Spain, coastal areas of Japan, South Korea and Pearl River of China (Taniyasu et al, 2003;So et al, 2004;Sánchez-Avila et al, 2010;Gómez et al, 2011). Higher concentrations of PFBS were found in coastal areas of the German Bight and South Korea (So et al, 2004;Ahrens et al, 2009b), and lower concentrations were observed in coastal areas of Japan, Catalonia in Spain (Taniyasu et al, 2003;Sánchez-Avila et al, 2010). Generally, the concentrations of PFBS in coastal waters were generally 1e2 orders of magnitude higher than that in open-ocean waters, which is similar to that of PFOA and PFOS.…”
Section: Comparison Of Pfc Concentrations In This Study With Those Insupporting
confidence: 83%
See 2 more Smart Citations
“…The concentration of PFBS in this study was comparable to that in other coastal regions, such as Catalonia and Cantabrian Sea in Spain, coastal areas of Japan, South Korea and Pearl River of China (Taniyasu et al, 2003;So et al, 2004;Sánchez-Avila et al, 2010;Gómez et al, 2011). Higher concentrations of PFBS were found in coastal areas of the German Bight and South Korea (So et al, 2004;Ahrens et al, 2009b), and lower concentrations were observed in coastal areas of Japan, Catalonia in Spain (Taniyasu et al, 2003;Sánchez-Avila et al, 2010). Generally, the concentrations of PFBS in coastal waters were generally 1e2 orders of magnitude higher than that in open-ocean waters, which is similar to that of PFOA and PFOS.…”
Section: Comparison Of Pfc Concentrations In This Study With Those Insupporting
confidence: 83%
“…On the other hand, the PFBS concentration exceed the PFOS concentration by about one order of magnitude in this study which can be explained by different emissions rates but also by its less bioaccumulation potential and less sorption potential to particles. The concentration of PFBS in this study was comparable to that in other coastal regions, such as Catalonia and Cantabrian Sea in Spain, coastal areas of Japan, South Korea and Pearl River of China (Taniyasu et al, 2003;So et al, 2004;Sánchez-Avila et al, 2010;Gómez et al, 2011). Higher concentrations of PFBS were found in coastal areas of the German Bight and South Korea (So et al, 2004;Ahrens et al, 2009b), and lower concentrations were observed in coastal areas of Japan, Catalonia in Spain (Taniyasu et al, 2003;Sánchez-Avila et al, 2010).…”
Section: Comparison Of Pfc Concentrations In This Study With Those Insupporting
confidence: 80%
See 1 more Smart Citation
“…Higher concentrations of PFCs in marine environments have often been associated with proximity to urban/industrial areas Keller et al, 2005;Kim & Kannan, 2007;So et al, 2004;Taniyasu et al, 2003;Yamashita et al, 2005). The objective of this study was to examine the impact of land use on the concentrations of PFOS and PFCAs detected in the plasma of bottlenose dolphins sampled in the estuarine waters in and around Charleston, SC.…”
Section: Introductionmentioning
confidence: 99%
“…Most of the research has focused on detection methods and technologies (Kuklenyik et al, 2004;Van Leeuwen et al, 2006;Yamashita et al, 2004), exposure characteristics Naile et al, 2010;Pan and You, 2010;Taniyasu et al, 2003), bioaccumulation (Shaw et al, 2009;Shi et al, 2012;Taniyasu et al, 2003) and toxic effects (Hoff et al, 2004;Ribes et al, 2010;Scialli et al, 2007). Nevertheless, limited attention has been given to the fate and transport of PFOS in multimedia environmental systems.…”
Section: Introductionmentioning
confidence: 99%